An Open Label Pre and Post Test Clinical Evaluation of Efficacy of Tila Taila Abhyanga and Massage of Yoni in Cystocele with Special Reference to Chyuta Avastha of Vasti (International Journal of Ayurveda and Pharma Research, 2022)
Prolapse or downward displacement of pelvic organs especially vagina, uterus and rectum is a common and disabling condition among women of menopausal age group. It affects their quality of life also. Displacement of vaginal anterior compartment results in cystocele. Quoting Acharya Susruta reference, the aim of this study is to find the efficacy of Tila taila yoni Abhyaṅga in Cyuta avastha of Vasti with respect to first degree cystocele. 30 subjects were selected satisfying inclusion and exclusion criterias with the approval of Institutional ethical committee. Clinical evaluation is done with the help of relevant subjective and objective parameters. The subjective parameters were assessed before and after the treatment for a period of one month with UDI questionnaire and objective parameter with Baden-Walker system of grading Pelvic Organ Prolapse. Three months follow-up evaluation was also done with same parameters. The Wilcoxon Signed Rank Test is used to statically decompose the clinical data. Subjective parameters showed improvement of the condition viz frequency and urgency of urination, urine leakage with and without any activity, cough, sneeze, small amount of urine leakage, difficult and incomplete bladder emptying, bulging in vagina However, leakage not related to urgency, lower abdominal pressure, painful urination and lower abdomen or genital area, pelvic area heaviness or dullness, pelvic discomfort and burning micturition showed only a little reduction with the treatment. Objective parameter is also highly statistically significant at p value < 0.001.